Peningkatan Sifat Mekanis Mortar Geopolimer Abu Terbang Batubara Dengan Penambahan Grafena - Rahmat Kurniawan Nasution; Amun Amri; Jhon Armedi Pinem (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
This study aims to observe the influence of graphene addition to the mechanical properties of coal fly ash based geopolymers. The procedure of research consisted of raw materials preparation including the graphene synthesis via Turbulence Assisted Shear Exfoliation (TASE) method, alkali activators solution preparation, and finally moulding and curing process of geopolymer mortar. The results showed that the compressive strength of geopolymer increased while the porosity and the water absorption decreased along with the addition of graphene. The highest compressive strength, the smallest porosity and the smallest water absorption, namely 15.228 MPa, 18.498 % and 10 % respectively was exhibited by sample synthesized using 20 mg/mL of graphene and curing temperature of 80 oC. The presence of graphene in the Geopolymer matrix increases the compressive strength properties of the Geopolymer mortar. Keywords : alkali activators, geopolymer, graphene, matrix, TASE